GAMBARAN PENGETAHUAN, KEPERCAYAAN MASYARAKAT DAN EFEK SAMPING PENGGUNAAN OBAT TRADISIONAL DI DUSUN HARANA DESA TANAMAKALEANG KECAMATAN SEKO KABUPATEN LUWU UTARA - Delta, Delta; Asti Trisnawati ,; Arinal Mulki Ahyar , (Journal of Innovation Research and Knowledge, 2025)
Traditional medicine is a herb that has been used for generations by the Indonesian people, utilizing various types of plants around us to overcome health problems. Some people also believe that traditional medicine has relatively lower side effects compared to modern medicine. The purpose of this research is to find out the overview of the level of knowledge and trust of the community and to find out the side effects on the use of traditional medicine in Harana Hamlet, Tanamakaleang Village, Seko District, North Luwu Regency. This study is a descriptive research using the cross sectional method and the research instrument used is a questionnaire that is distributed directly to the respondents. The sampling technique used is the purposive sampling technique. The number of samples in this study was 70 respondents. The data analysis technique in this study uses the SPSS program. The results of the study found that the majority of respondents had good knowledge (74.3%), and a high level of trust (94.3%). The percentage of respondents who did not feel side effects was 94.3% and as many as 5.7% of respondents felt side effects. The side effect that many respondents felt was digestive system disorders. The suggestion in this study is that the public is expected to increase knowledge related to the use of traditional medicine, including its benefits and side effects. In addition to paying attention to the experiences of others, the public is also advised to seek information from health workers.